ATP‐independent molecular chaperone activity generated under reducing conditions. (13th July 2022) - Leppert, Axel; Chen, Gefei; Lianoudaki, Danai; Williams, Chloe; Zhong, Xueying; Gilthorpe, Jonathan D.; Landreh, Michael; Johansson, Jan
Abstract: Molecular chaperones are essential to maintain proteostasis. While the functions of intracellular molecular chaperones that oversee protein synthesis, folding and aggregation, are established, those specialized to work in the extracellular environment are less understood. Extracellular proteins reside in a considerably more oxidizing milieu than cytoplasmic proteins and are stabilized by abundant disulfide bonds. Hence, extracellular proteins are potentially destabilized and sensitive to aggregation under reducing conditions. We combine biochemical and mass spectrometry experiments and elucidate that the molecular chaperone functions of the extracellular protein domain Bri2 BRICHOS only appear under reducing conditions, through the assembly of monomers into large polydisperse oligomers by an intra‐ to intermolecular disulfide bond relay mechanism. Chaperone‐active assemblies of the Bri2 BRICHOS domain are efficiently generated by physiological thiol‐containing compounds and proteins, and appear in parallel with reduction‐induced aggregation of extracellular proteins. Our results give insights into how potent chaperone activity can be generated from inactive precursors under conditions that are destabilizing to most extracellular proteins and thereby support protein stability/folding in the extracellular space. Significance: Chaperones are essential to cells as they counteract toxic consequences of protein misfolding particularly under stress conditions. Our work describes a novel activation mechanism of an extracellular molecular chaperone domain, called Bri2 BRICHOS. This mechanism is based on reducing conditions that initiate small subunits to assemble into large oligomers via a disulfide relay mechanism. Activated Bri2 BRICHOS inhibits reduction‐induced aggregation of extracellular proteins and could be a means to boost proteostasis in the extracellular environment upon reductive stress.